An emergency responding mechanism for cruise epidemic prevention—taking COVID-19 as an example - Liu, Xiaofei (Mar Policy, 2020)
COVID-19 has severely impacted the global cruise tourism industry. The increasing number of confirmed cases during the quarantine period of ‘Diamond Princess’ questioned the efficiency and science behind the Japanese government's emergency management of the outbreak and led to a debate on the responsibilities of the ship's country of registry and port country. In order to deal with the spread of virus on a cruise ship rationally, the present study analyses why cruise ships are more prone to an emergent epidemic and discusses requirements of international conventions and domestic laws on cruise ship sanitation and epidemic prevention. It also evaluates the rescue responsibility of Flag State and Port State, explores the legal lacunae of international conventions on the rescue obligation of cruise home port, and provides solutions for prevention and control of cruise ship epidemic with short-term response measures and long-term mechanism construction. In terms of a short-term response, it is vital to adopt the quarantine idea of a ‘temporary cabin hospital’ and a disposal procedure of ‘circular disinfection-section repeat testing-batch transfer and quarantine-international collaborative medical treatment’. For a long-term mechanism construction, three aspects need to be considered: the risk emergency management mechanism of cruise lines, health and epidemic prevention supervision mechanisms, and international cooperation mechanisms of infectious disease prevention.